Sodium Meta-Arsenite Ameliorates Hyperglycemia in Obese Diabetic db/db Mice by Inhibition of Hepatic Gluconeogenesis - Young-Sun Lee; Eun-Kyu Lee; Hyun-Hee Oh; Cheol Soo Choi; Sujong Kim; Hee-Sook Jun (Journal of Diabetes Research)
Sodium meta-arsenite (SA) is implicated in the regulation of hepatic gluconeogenesis-related genes in vitro; however, the effects in vivo have not been studied. We investigated whether SA has antidiabetic effects in a type 2 diabetic mouse model. Diabetic db/db mice were orally intubated with SA (10 mg kg−1 body weight/day) for 8 weeks. We examined hemoglobin A1c (HbA1c), blood glucose levels, food intake, and body weight. We performed glucose, insulin, and pyruvate tolerance tests and analyzed glucose production and the expression of gluconeogenesis-related genes in hepatocytes. We analyzed energy metabolism using a comprehensive animal metabolic monitoring system. SA-treated diabetic db/db mice had reduced concentrations of HbA1c and blood glucose levels. Exogenous glucose was quickly cleared in glucose tolerance tests. The mRNA expressions of genes for gluconeogenesis-related enzymes, glucose 6-phosphatase (G6Pase), and phosphoenolpyruvate carboxykinase (PEPCK) were significantly reduced in the liver of SA-treated diabetic db/db mice. In primary hepatocytes, SA treatment decreased glucose production and the expression of G6Pase, PEPCK, and hepatocyte nuclear factor 4 alpha (HNF-4α) mRNA. Small heterodimer partner (SHP) mRNA expression was increased in hepatocytes dependent upon the SA concentration. The expression of Sirt1 mRNA and protein was reduced, and acetylated forkhead box protein O1 (FoxO1) was induced by SA treatment in hepatocytes. In addition, SA-treated diabetic db/db mice showed reduced energy expenditure. Oral intubation of SA ameliorates hyperglycemia in db/db mice by reducing hepatic gluconeogenesis through the decrease of Sirt1 expression and increase in acetylated FoxO1.